2018
DOI: 10.1103/physreve.97.063205
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear excitation by electron capture in optical-laser-generated plasmas

Abstract: The process of nuclear excitation by electron capture in plasma environments generated by the interaction of ultrastrong optical lasers with solid-state samples is investigated theoretically. With the help of a plasma model, we perform a comprehensive study of the optimal parameters for the most efficient nuclear excitation and determine the corresponding laser setup requirements. We discern between the low-density plasma regime, modeled by scaling laws, and the high-density regime, for which we perform partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 69 publications
0
39
0
Order By: Relevance
“…However, the comparison with the more detailed hydrodynamic expansion model in Ref. [37] has shown that this lifetime approximation provides reasonable NEEC results, with a ∼ 50% of deviation for the case of low temperatures and ∼ 5% for high temperatures ( 6 keV). In addition, our calculations here predict that both the NEEC rate and the resulting number of excited nuclei have a smooth dependence on density and temperature.…”
Section: B Number Of Depleted Isomersmentioning
confidence: 84%
See 4 more Smart Citations
“…However, the comparison with the more detailed hydrodynamic expansion model in Ref. [37] has shown that this lifetime approximation provides reasonable NEEC results, with a ∼ 50% of deviation for the case of low temperatures and ∼ 5% for high temperatures ( 6 keV). In addition, our calculations here predict that both the NEEC rate and the resulting number of excited nuclei have a smooth dependence on density and temperature.…”
Section: B Number Of Depleted Isomersmentioning
confidence: 84%
“…As a general feature of NEEC, capture is most efficient and the excitation cross sections are highest for electron recombination into inner-shell vacancies. This holds true also for the case of 93m Mo, for which the largest NEEC cross section occurs for the capture into the L-shell vacancies, while capture into the inner-most K-shell is energetically forbidden [24,25,36,37]. However, in a plasma scenario it is difficult to simultaneously facilitate both the existence of inner-shell vacancies and the corresponding free electron energies that are allowed by NEEC.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations